Criminal Law Policy As An Effort Of Overcoming Crime Towards Protected Animals - Benny Karya Limantara; Bambang Hartono (Bandar Lampung University, 2015)
This research discusses about criminal law policy in determining direction of the criminal offense prevention policy protected animals now in Indonesia and in the foreseeable future. The study was based on the results of research in normative jurisdiction to find a norms and principle in formulating the protection of animals. The research concludes the protection of animals are still in effective, such as the lack of accountability for corporate regulation and the absence of a regulation on sanctions difference between animals from the nature and captive breeding. therefore, there needs to reformulation of the Law of Conservation of Natural Resources and Ecosystem, and the inclusion of regulation of protected animals in the Draft Criminal Code as a new juridical basis to provide the protection both in concretely and abstractly.